Perfects and iamitives: two gram types in one grammatical space - Dahl, Östen; Wälchli, Bernhard (Letras de Hoje, 2016)
This paper investigates the grammatical space of the two gram types – perfects and iamitives. Iamitives (from Latin iam ‘already’) overlap in their use with perfects but differ in that they can combine with stative predicates to express a state that holds at reference time. Iamitives differ from ‘already’ in having a higher frequency and showing a strong tendency to be grammaticalized with natural development predicates. We argue that iamitives can grammaticalize from expressions for ‘already’. In this study, we extract perfect grams and iamitive grams iteratively starting with two groups of seed grams from a parallel text corpus (the New Testament) in 1107 languages. We then construct a grammatical space of the union of 370 extracted grams by means of Multidimensional Scaling. This grammatical space of perfects and iamitives turns out to be a continuum without sharp boundaries anywhere. ******************************************************************** Perfeitos e iamitivos: dois tipos de gram em um espaço gramatical Resumo: Este artigo investiga o espaço gramatical de dois tipos de gram – perfeitos e iamitivos. Iamitivos (do latim iam “já”) sobrepõem-se em seu uso com perfeitos, mas diferem naquilo em que podem combinar-se com predicados estativos que expressem um estado detentor de referência temporal. Iamitivos diferenciam-se de “já” por apresentarem maior frequência e forte tendência à gramaticalização com desenvolvimento natural de predicados. Argumenta-se que iamitivos podem gramaticalizar a partir de expressões para “já”. Neste estudo, extraemse grams perfeitos e grams iamitivos iterativamente, começando com dois grupos de grams disseminados de um texto de corpus paralelo (o Novo Testamento) em 1107 línguas. Em seguida, constrói-se um espaço gramatical da união de 370 grams extraídos por meio de Escalonamento Multidimensional. Tal espaço gramatical de perfeitos e iamitivos acaba mostrando-se um contínuo sem fronteiras nítidas em qualquer lugar. Palavras-chave: Perfeito; Iamitivo; Gram (tipo); Espaço gramatical; Texto paralelo; Distribuição generalizada; Escalonamento Multidimensional; Gramaticalização; Desenvolvimento natural; Transição para novo cenário; Período de tempo prolongado